The Influence of the Characteristics of the Board of Directors on the Sustainability Performance of Islamic Banking in Indonesia - Rani, Inggar Dwi (SAINTIS Publishing, 2025)
This study aims to analyze and examine the influence of the characteristics of the board of directors which include the size of the board of directors, board of directors-meetings and the age of the board of directors on sustainability performance with institutional ownership as a moderator. This study uses a quantitative method with data taken from Sharia Commercial Banks in Indonesia registered with the Financial Services Authority (OJK) for the period 2017 to 2023 which have issued annual reports and sustainability reports. Sample selection was carried out using the purposive sampling method and the data was analyzed using panel data regression techniques and Moderate Regression Analyze (MRA). The results of his research show that the size and meetings of the board of directors have a significant and positive influence on sustainability performance, while the age of the board of directors has no effect on sustainable performance. The results of the study also show that institutional ownership is not able to moderate or strengthen the relationship between board of directors-characteristics and sustainability performance Extensive empirical evidence has examined the relationship between corporate governance variables and sustainability performance. This research deepens by focusing on the influence of the characteristics of the board of directors (size, meetings, and age of the board of directors) on the sustainability performance of Sharia Commercial Banks in Indonesia and adding the institutional ownership variable as a moderator.